The MYB family transcription factor TuODORANT1 from Triticum urartu and the homolog TaODORANT1 from Triticum aestivum inhibit seed storage protein synthesis in wheat. Issue 9 (5th June 2021) - Luo, Guangbin; Shen, Lisha; Song, Yanhong; Yu, Kang; Ji, Jingjing; Zhang, Chi; Yang, Wenlong; Li, Xin; Sun, Jiazhu; Zhan, Kehui; Cui, Dangqun; Wang, Yanpeng; et al.
Summary: Seed storage proteins (SSPs) are determinants of wheat end‐product quality. SSP synthesis is mainly regulated at the transcriptional level. Few transcriptional regulators of SSP synthesis have been identified in wheat and this study aims to identify novel SSP gene regulators. Here, the R2R3 MYB transcription factor TuODORANT1 from Triticum urartu was found to be preferentially expressed in the developing endosperm during grain filling. In common wheat ( Triticum aestivum ) overexpressing TuODORANT1, the transcription levels of all the SSP genes tested by RNA‐Seq analysis were reduced by 49.71% throughout grain filling, which contributed to 13.38%–35.60% declines in the total SSP levels of mature grains. In in vitro assays, TuODORANT1 inhibited both the promoter activities and the transcription of SSP genes by 1‐ to 13‐fold. The electrophoretic mobility shift assay (EMSA) and ChIP‐qPCR analysis demonstrated that TuODORANT1 bound to the cis ‐elements 5′‐T/CAACCA‐3′ and 5′‐T/CAACT/AG‐3′ in SSP gene promoters both in vitro and in vivo . Similarly, the homolog TaODORANT1 in common wheat hindered both the promoter activities and the transcription of SSP genes by 1‐ to 112‐fold in vitro . Knockdown of TaODORANT1 in common wheat led to 14.73%–232.78% increases in the transcription of the tested SSP genes, which contributed to 11.43%–19.35% elevation in the total SSP levels. Our data show that both TuODORANT1 and TaODORANT1 are repressors of SSP synthesis.